The Theory of Optimal Delegation With an Application to Tariff Caps - Amador, Manuel; Bagwell, Kyle (Econometrica, 2013)
We consider a general representation of the delegation problem, with and without money burning, and provide sufficient and necessary conditions under which an interval allocation is optimal. We also apply our results to the theory of trade agreements among privately informed governments. For both perfect and monopolistic competition settings, we provide conditions under which tariff caps are optimal. [PUBLICATION ABSTRACT]